(3TQM GdcGajIs - (3GdQVi eMeO Hf GdMSf GdCSJQGHGPjs; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s ((3HOQGdOjf eMehO Hf CMeO GdYjfj s)
(3ChdgG (B:s
(3hHYO, abO WdH Edj ef GYJfi HUdGM MGdg, hCSYag HeG JSYg ebOQJj ef ebJQMGJ BeGdg s
(3BNQgG (B:s
(3bGd JYGdi (B: "(3gfGdc GdhdGjI ddg(B" (3Je GdLRA GdChd s
(3eged GdfbW CMjGfkGs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs